Sustainable intensification assessment framework online toolkit - Stewart, Zachary P.; Middendorf, B. Jan; Vara Prasad, P.V.V. (Kansas State University, 2018)
The SI Toolkit is an interactive method to assess your research in sustainable intensification and adapt your practices to achieve the best possible outcome for all parts of a smallholder farmer’s system.